2020
DOI: 10.1186/s12977-020-00520-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-active site mutants of HIV-1 protease influence resistance and sensitisation towards protease inhibitors

Abstract: Background: HIV-1 can develop resistance to antiretroviral drugs, mainly through mutations within the target regions of the drugs. In HIV-1 protease, a majority of resistance-associated mutations that develop in response to therapy with protease inhibitors are found in the protease's active site that serves also as a binding pocket for the protease inhibitors, thus directly impacting the protease-inhibitor interactions. Some resistance-associated mutations, however, are found in more distant regions, and the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 78 publications
1
16
0
1
Order By: Relevance
“…However, several studies showed that some thermodynamic couplings persist over large distances in space, which can not be explained by direct interactions of the corresponding amino acids. The long-range mutation effects in proteins are of particular interest as they may have significant contributions to enzymatic activity, , protein folding, or ligand binding affinity . In coevolution analyses coupled mutations can be traced down by multiple sequence alignments.…”
mentioning
confidence: 99%
“…However, several studies showed that some thermodynamic couplings persist over large distances in space, which can not be explained by direct interactions of the corresponding amino acids. The long-range mutation effects in proteins are of particular interest as they may have significant contributions to enzymatic activity, , protein folding, or ligand binding affinity . In coevolution analyses coupled mutations can be traced down by multiple sequence alignments.…”
mentioning
confidence: 99%
“…Earlier studies have shown that intrinsic changes in the HIV-1 PR conformation associated with the accumulation of drug-resistant mutations may cause geometric alteration in the HIV-1 PR structure affecting the active site and other domains [61,77]. These intrinsic changes may cause sensitization and cross-resistance to HIV-1 PIs by altering the molecular interaction of the former with the protein during binding [16,77]. The evolution of these characteristics in proteins is often associated with the loss of protein stability [80].…”
Section: Discussionmentioning
confidence: 99%
“…The gain in HIV-1 PR flexibility due to changes in inter-residue Drug-resistance mutations could be found in the active site of HIV-1 PR and directly impact the binding affinity and interaction of HIV-1 PIs with HIV-1 PR [15]. In contrast, non-active site mutations may not directly affect the interaction of HIV-1 PR with inhibitors but may indirectly influence the molecular interaction of inhibitors with the HIV-1 PR through alteration of the protein flexibility and stability [16][17][18]. The accumulation and interplay between active and non-active site drug-resistance mutations arising from drug pressure may cause structural changes, leading to HIV-1 PR variants with altered protein conformations [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 17 , 18 , 19 , 20 , 21 , 22 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 63 , 64 .…”
Section: Uncited Referencesunclassified